Nanomedicines, a strategy to evade multidrug resistance - Pereira, Carolina Correia de Figueiredo Abreu (2015)
Multidrug resistance is a major problems associated with cancer chemotherapy. Efflux transports is one of the numerous mechanisms involved in multidrug resistance. P-glycoprotein is a transmembrane protein, responsible for drug efflux, which decreases drugs intracellular bioavailability, consequently decreasing their efficacy against cancer. Cancer growth and dissemination depends on the expression of transcriptional factors such as, Twist. Among other features, this protein is related with cells chemoresistance possible by regulation of multidrug resistance pathways including the P-glycoprotein expression. The herein study proposes to demonstrate if paclitaxel entrapped nanoparticles is an effective system in evading multidrug resistance mechanisms and if functionalization of a specific antibody against cancer stem cells receptors (anti-CD44v6) has the capability to target selectively these cells increasing nanoparticles efficacy. Therefore solid lipid nanoparticles were prepared and a breast cancer cell line (MDA-MB-436) was exposed to them in order to assess unloaded nanoparticles cytotoxic effects, increased pharmacologic efficacy of loaded nanoparticles relative to the free drug and their ability to evade multidrug resistance. The proposed solid lipid nanoparticles system proved to be capable of efficiently evading multidrug resistance mechanisms; however no improvement was added when these nanoparticles were functionalized with the antibody in the in vitro studies. However, the nanoparticles system is effective against multidrug resistance mechanisms.